Characteristics of Formation of Ethnoponyms of Fergana Region - Jo‘raboyeva Gulrux Solijonovna; Tursunov Asadullo Shuhratjon o‘g‘li (Zien Journals, 2023)
The article examines the types of ethnotoponyms existing in the Fergana region, according to their structure, and the characteristics of their formation.
Keywords: toponym; ethnonym; ethnotoponym